CAR-T cells and TRUCKs that recognize an EBNA-3C-derived epitope presented on HLA-B*35 control Epstein-Barr virus-associated lymphoproliferation. Issue 2 (30th October 2020) - Dragon, Anna Christina; Zimmermann, Katharina; Nerreter, Thomas; Sandfort, Deborah; Lahrberg, Julia; Klöß, Stephan; Kloth, Christina; Mangare, Caroline; Bonifacius, Agnes; Tischer-Zimmermann, Sabine; Blasczyk, Rainer; Maecker-Kolhoff, Britta; et al.
Abstract : Background: Immunosuppressive therapy or T-cell depletion in transplant patients can cause uncontrolled growth of Epstein-Barr virus (EBV)-infected B cells resulting in post-transplant lymphoproliferative disease (PTLD). Current treatment options do not distinguish between healthy and malignant B cells and are thereby often limited by severe side effects in the already immunocompromised patients. To specifically target EBV-infected B cells, we developed a novel peptide-selective chimeric antigen receptor (CAR) based on the monoclonal antibody TÜ165 which recognizes an Epstein-Barr nuclear antigen (EBNA)−3C-derived peptide in HLA-B*35 context in a T-cell receptor (TCR)-like manner. In order to attract additional immune cells to proximity of PTLD cells, based on the TÜ165 CAR, we moreover generated T cells redirected for universal cytokine-mediated killing (TRUCKs), which induce interleukin (IL)-12 release on target contact. Methods: TÜ165-based CAR-T cells (CAR-Ts) and TRUCKs with inducible IL-12 expression in an all-in-one construct were generated. Functionality of the engineered cells was assessed in co-cultures with EBNA-3C-peptide-loaded, HLA-B*35-expressing K562 cells and EBV-infected B cells as PTLD model. IL-12, secreted by TRUCKs on target contact, was further tested for its chemoattractive and activating potential towards monocytes and natural killer (NK) cells. Results: After co-cultivation with EBV target cells, TÜ165 CAR-Ts and TRUCKs showed an increased activation marker expression (CD137, CD25) and release of proinflammatory cytokines (interferon-γ and tumor necrosis factor-α). Moreover, TÜ165 CAR-Ts and TRUCKs released apoptosis-inducing mediators (granzyme B and perforin) and were capable to specifically lyse EBV-positive target cells. Live cell imaging revealed a specific attraction of TÜ165 CAR-Ts around EBNA-3C-peptide-loaded target cells. Of note, TÜ165 TRUCKs with inducible IL-12 showed highly improved effector functions and additionally led to recruitment of monocyte and NK cell lines. Conclusions: Our results demonstrate that TÜ165 CAR-Ts recognize EBV peptide/HLA complexes in a TCR-like manner and thereby allow for recognizing an intracellular EBV target. TÜ165 TRUCKs equipped with inducible IL-12 expression responded even more effectively and released IL-12 recruited additional immune cells which are generally missing in proximity of lymphoproliferation in immunocompromised PTLD patients. This suggests a new and promising strategy to specifically target EBV-infected cells while sparing and mobilizing healthy immune cells and thereby enable control of EBV-associated lymphoproliferation.